DEVELOPMENT OF DISTRIBUTED CONCEPTUAL HYDROLOGICAL MODEL FOR FOREST WATERSHED IN NORTHERN THAILAND: A DOWNWARD APPROACH - Wichan Phandee; Chatchai Jothityangkoon; Songkot Dasananda (European Scientific Journal, ESJ, 2014)
This paper reports promising use of the downward approach in the construction of the distributed conceptual hydrological models for a forest watershed in Chiang Mai Province, northern Thailand, at monthly and daily time scales with 30-m spatial resolution. It was found that the built models have exhibited impressive capability in the simulation of actual runoff yield with R2 and the Nash-Sutcliffe efficiency index (E) of 0.94 and 0.88 (for the optimal monthly model), and 0.96 and 0.94 (for the optimal daily model), respectively. The applied water balance system with three main hydrological processes; surface runoff, subsurface runoff, and evapotranspiration (ET), was proved to be sufficient in explaining general runoff characteristics of the area at both studied scales, especially during strong monsoon months from August to October. Obtained results from the monthly cases indicate that rainfall variation plays more important role than the soil depth heterogeneity in producing more realistic pattern of the runoff product and integration of subsurface runoff process was found vital in the development of successful model. In addition, sole use of the evaporation component of ET was found sufficient in building the successful monthly model but in case of the daily model, the transpiration part was also necessary.